Optimization of a culture medium based on forage palm for δ-endotoxin production. (August 2020) - da Silva, Túlio Alexandre Freire; Freitas, Lívia Santos de; da Silva, Larita Veruska José Bezerra; Duarte Neto, José Manoel Wanderley; da Silva, Gilvanda Ribeiro; Maranhão, Liane Maria de Almeida Castro; Coitinho, Rodrigo Leandro Braga de Castro; de Lacerda, Cynthia Araújo; Oliveira, José de Paula; Bezerra, Raquel Pedrosa; Porto, Ana Lúcia Figueiredo
Abstract: An alternative culture medium based on forage palm (Cactaceae) and inexpensive nitrogen sources for δ-endotoxin production by Bacillus thuringiensis var. berliner (Btb) was optimized using response surface methodology and the influence of the nitrogen sources on biological activity and morphological properties of the δ-endotoxin has been studied. Effects of forage palm extract concentration (15–25%), ammonium sulphate (0–1 g/L), ammonium chloride (0–1 g/L) and urea concentrations (0–1 g/L) on δ-endotoxin production were studied by a 2 4 full factorial design and optimized by a 2 2 central composite design (CCD). Statistical analysis showed that forage palm and ammonium sulphate were the main factors to enhance δ-endotoxin production. Different nitrogen sources influenced on biological activity and morphology of crystals. Culture medium constituted by forage palm extract and ammonium sulphate increased δ-endotoxins production in the form of bipyramidal crystals and was more toxic to Spodoptera frugiperda . Forage palm extract and ammonium sulphate were considered to optimization of δ-endotoxin production. Maximum δ-endotoxin production (356 mg/L) took place at 30.7% (w/v) of forage palm extract concentration and 1.016 g/L of ammonium sulphate. Highlights: δ-endotoxins were produced in an inexpensive forage palm-based culture medium. N. cochenillifera is more appropriate as a carbon source to δ-endotoxin production. Ammonium sulphate increases the δ-endotoxin production and its toxicity. The optimum medium had 30.7% N. cochenillifera and 1.016 g/L ammonium sulphate. Optimum culture medium allowed the production of 356 mg/L of δ-endotoxin.